IN VITRO CULTURE OF FOREIGN AND LOCAL PANICUM VIRGATUM AND PANICUM MILIACEUM CULTIVARS - Rakhimzhanova , A.O.; Bekkuzhina , S.S.; Zhumabek , A.T.; Ramankulov , Ye.M.; Manabayeva , Sh.A. (Eurasian Journal of Applied Biotechnology, 2018)
The development of effective methods for obtaining sterile cultures and identification of explants with high morphogenetic potential are the basis for the implementation of biotechnological methods used in plant breeding programs. Local and foreign varieties of P. miliaceum and P. virgatum were used to improve the qualitative and quantitative characteristics of Panicum. Panicum seeds provided a 100% yield of sterile explants and were found to be more effective than sprouts. The callus-forming potential of Panicum seeds was high: Kormovoe variety 2014 were 97%, Forestburg variety were 94% and cotyledon explants were 29%. Intensive morphogenic callus formation was observed on MS basal medium containing B5 vitamins without exogenous hormons. In addition, our experiments attempted the rotation of Panicum culture on solid and liquid media for the induction of embryonic structures and increased regeneration potential. Combined surface and deep culturing of callus tissues led to an increased frequency of embryonic structures. The results of these experimental studies can be used for further development of genetic engineering techniques, for structural transfers in embryogenic tissues, and for the regeneration of transgenic plants.